2010
DOI: 10.1007/s10658-010-9586-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a mechanical transmissible begomovirus causing leaf curl on oriental melon

Abstract: Oriental melon plants, Cucumis melo var. makuwa cv. Silver Light, showing virus-induced symptoms of mosaic, leaf curl and puckering were observed in the fields of eastern Taiwan in 2007. A virus culture, designated as SL-1, isolated from the diseased melon was established in systemic host plants, Nicotiana benthamiana and oriental melon, by mechanical inoculation. SL-1 did not react to the antisera against common cucurbit-infecting RNA viruses. Viral DNAs extracted from the diseased plant were amplified with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…It has been speculated that differences between isolates in the length of the nuclear shuttle protein (NSP) may account for these differences. Mechanically transmissible isolates had shorter NSPs because of the loss of amino-acids in the N terminus, which has been shown to be decisive in symptom development and as a virulence determinant (Chang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been speculated that differences between isolates in the length of the nuclear shuttle protein (NSP) may account for these differences. Mechanically transmissible isolates had shorter NSPs because of the loss of amino-acids in the N terminus, which has been shown to be decisive in symptom development and as a virulence determinant (Chang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (2010) reported the mechanical transmission of a ToLCNDV isolate from Taiwan (ToLCNDV-OM) found in oriental melons (Cucumis melo var. makuwa, variety included in the group conomon of the subspecies agrestis) to the original host, to other accessions of the conomon group, and to four other cucurbits: bottle gourd, cucumber, zucchini squash, and sponge gourd.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations